1997
DOI: 10.1038/sj.ijir.3900271
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind, placebo-controlled safety and efficacy trial with yohimbine hydrochloride in the treatment of nonorganic erectile dysfunction

Abstract: This double-blind, placebo-controlled clinical trial of yohimbine hydrochloride included 86 patients with erectile dysfunction and without clearly detectable organic or psychologic causes. The patient group ful®lled all entry criteria; 85 of these could be considered for the Safetyrespectively 83 for the Intention-to-treat (ITT)-analysis. Yohimbine was administered orally in a dosage of 30 mg a day (two 5mg tablets three times daily) for eight weeks. Patients were seen for follow-up after four weeks' treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 6 publications
(9 reference statements)
1
24
0
7
Order By: Relevance
“…Apomorphine may be less effective compared to sildenafil and its adverse effects, especially nausea and fatigue, will often limit its use. In patients suffering from psychogenic ED, yohimbine may ameliorate erection [140]. …”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…Apomorphine may be less effective compared to sildenafil and its adverse effects, especially nausea and fatigue, will often limit its use. In patients suffering from psychogenic ED, yohimbine may ameliorate erection [140]. …”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…12 Several authors have shown that the treatment of nonorganic ED with the alpha-2-antagonist yohimbine hydrochloride is safe and effective. 13 However, a host of organic side effects have been recorded in association with the use of yohimbine. Therefore, the question arises of whether the treatment of ED through the administration of yohimbine outweighs the risks associated with this drug.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were supported by pervious sophisticated results which concerned with examination of yohimbine-induced relaxation in human and rabbit corpora cavernosa through interfering with NO release from the endothelium. The yohimbine-induced corpus cavernosum relaxation was inhibited by mechanical removal of the endothelium and by blocking NO formation or signaling via guanylate cyclase and cGMP formation [20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Yohimbine was found to be beneficial and effective in treatment of psychogenic and/or organic erectile dysfunction when taken in divided daily doses [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%